The Downward Influence of Stratospheric Sudden Warmings - Hitchcock, Peter; Simpson, Isla R. (2014)
The coupling between the stratosphere and the troposphere following two major stratospheric sudden warmings is studied in the Canadian Middle Atmosphere Model using a nudging technique by which the zonal-mean evolution of the reference sudden warmings are artificially induced in an ~100-member ensemble spun off from a control simulation. Both reference warmings are taken from a freely running integration of the model. One event is a displacement, the other is a split, and both are followed by extended recoveries in the lower stratosphere. The methodology permits a statistically robust study of their influence on the troposphere below. The nudged ensembles exhibit a tropospheric annular mode response closely analogous to that seen in observations, confirming the downward influence of sudden warmings on the troposphere in a comprehensive model. This tropospheric response coincides more closely with the lower-stratospheric annular mode anomalies than with the midstratospheric wind reversal. In addition to the expected synoptic-scale eddy feedback, the planetary-scale eddies also reinforce the tropospheric wind changes, apparently responding directly to the stratospheric anomalies. Furthermore, despite the zonal symmetry of the stratospheric perturbation, a highly zonally asymmetric near-surface response is produced, corresponding to a strongly negative phase of the North Atlantic Oscillation with a much weaker response over the Pacific basin that matches composites of sudden warmings from the Interim ECMWF Re-Analysis (ERA-Interim). Phase 5 of the Coupled Model Intercomparison Project models exhibit a similar response, though in most models the response’s magnitude is underrepresented.